The Effect of Compensation and Work Environment on Work Discipline and Performance of Mini Mart Employees in Denpasar City - Sukarta Wirya, Komang Edy (Jurnal Ekonomi dan Bisnis Jagaditha, 2019)
This research aims to analyze and explain the influence of compensation, and work environment to work discipline and employee performance Mini Mart in Denpasar City. The sample of the study is from all employees of the operational department, especially the commercial staff who work in Mini Mart Denpasar City that is as many as 35 employees. The data are primary data obtained from the questionnaire to find out the respondent's perception about the variables studied and secondary data obtained from books, references, documents and other information available in Mini Mart in Denpasar City. Testing research hypothesis is done using Partial Least Square (PLS) application. The results showed that compensation has a positive and significant effect on work discipline. Work environment have positive and significant effect to work discipline. Compensation has a positive and significant effect on performance. The work environment has a positive and significant impact on performance. Work discipline has a positive and significant impact on performance. Work discipline mediates partially between compensation and performance, and the work discipline mediates partially between the working environment and the performance of employees of Mini Mart Denpasar